Bi-Layered, Ultrathin Coating Initiated Relay Response to Impart Superior Fire Resistance for Polymeric and Metallic Substrates - Tang, Wei; Chen, Qi; Li, Junxiao; Ao, Xiang; Liu, Yunhuan; Qian, Lijun; Prolongo, Silvia González; Qiu, Yong; Wang, De‑Yi (Nano-Micro Letters, 2025)
Developing high-efficient flame-retardant coatings is crucial for fire safety polymer and battery fields. Traditional intumescent coatings and ceramifiable coatings struggle to provide immediate and prolonged protection simultaneously, which limits the applicability. To address this, an innovative bi-layered coating with organic/nano-inorganic additives is inspired by differential response behaviors, enabling relay response effect with both fast-acting and extended protection. Specifically, two layers function continuously in the form of a relay. With a mere 320 microns, the bi-layered coating withstands fire temperatures of up to 1400 °C for at least 900 s. Consequently, the coating effective prevented burn through in aluminum plates and glass fabric-reinforced epoxy resin, which otherwise were burned through in 135 and 173 s, respectively. Meanwhile, the bi-layered coating suppressed the formation and decomposition of solid interface layer in lithium soft-package batteries, leading to prolonged electrochemical stability and fire safety. Additionally, the bi-layered coating with a fast response endows polyurethane foam with rapid self-extinguishing, preventing ignition even under exposure to strong fire of 1400 °C. Shortly, our work offers new insights into the design and development of thin, high-performance, and multi-application flame-retardant coatings. Highlights: 1 Relay response of bi-layered coating achieved fast response and extended protection. 2 320-µm coating achieved over 900 s of burn-through resistance. 3 320-µm coating achieved extended electrochemical stability for battery under fire.